Ensino e aprendizagem de Análise Combinatória: uma proposta a partir do uso de histórias interativas no ambiente Scratch - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This work aims to present potentials and possibilities of the usage of interactive stories, produced in the Scratch environment, in the study of Combinatorial Analysis. For this purpose, qualitative research assumptions were used, initially analyzing research results on the development of combinatorial reasoning and its teaching and learning process, and thus, understanding what is being proposed in theoretical and methodological terms for improvement of the performance of students and teachers in this field. These were followed by deepenings related to Combinatorics, through formal definitions and respective examples. Followed by the development of a website (Google Sites Platform) that presents a set of interactive stories (8 in total), produced in the Scratch environment, exposing different types of Combinatorics problems (Arrangement, Combination and Permutation), emphasizing the multiplicative and additive principles, as a resolution strategy, and the possibilities tree as a resolution strategy and graphical representation. With the elaboration of this work, it was possible to verify that the tools available in Scratch offer countless possibilities of creations for the study of Combinatorial Analysis. In particular, in the construction of interactive stories, it is possible to use “actors” movement resources for the elaboration of problem solving strategies, which allows some generalizations and mobilization of these strategies in several other problems. This is important, because in many problems the solution formulas are inefficient (it is not possible to apply the rule directly), making it necessary to have different strategies.
Keywords: Raciocínio Combinatório; Princípios Multiplicativo e Aditivo; Árvore de Possibilidades; Scratch; Histórias Interativas; Combinatorial reasoning; Multiplication and Addition Principles; Interactive Stories; Tree Diagrams.; CNPQ::CIENCIAS EXATAS E DA TERRA